2015
DOI: 10.1021/acsami.5b03522
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Power Generation from Lanthanum Strontium Titanium Oxide at Room Temperature through the Addition of Graphene

Abstract: The applications of strontium titanium oxide based thermoelectric materials are currently limited by their high operating temperatures of >700 °C. Herein, we show that the thermal operating window of lanthanum strontium titanium oxide (LSTO) can be reduced to room temperature by the addition of a small amount of graphene. This increase in operating performance will enable future applications such as generators in vehicles and other sectors. The LSTO composites incorporated one percent or less of graphene and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 177 publications
(125 citation statements)
references
References 43 publications
8
116
1
Order By: Relevance
“…Below 800 K the electrical conductivity and the Seebeck coefficient of polycrystalline STO (without graphene) are beyond the limits of the instruments used here. Literature data sources: lanthanum doped STO single crystal (LSTO SC), reduced graphene oxide/STO nanocomposite (RGO/STO), graphene/lanthanum doped STO nanocomposite (G/LSTO), reduced graphene oxide/niobium doped STO nanocomposite (RGO/NSTO) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Below 800 K the electrical conductivity and the Seebeck coefficient of polycrystalline STO (without graphene) are beyond the limits of the instruments used here. Literature data sources: lanthanum doped STO single crystal (LSTO SC), reduced graphene oxide/STO nanocomposite (RGO/STO), graphene/lanthanum doped STO nanocomposite (G/LSTO), reduced graphene oxide/niobium doped STO nanocomposite (RGO/NSTO) …”
Section: Resultsmentioning
confidence: 99%
“…The grain boundary effect is significantly reduced with the addition of only 0.11 vol% pristine graphene, and the weighted mobility matches that of single crystals above 700 K. At higher graphene concentrations (around 0.22 vol%,) the grain boundary effect is completely eliminated above room temperature. The weighted mobilities of the G/STO, G/LSTO, [27] and RGO/ NSTO [28] nanocomposites are the same as that of STO single crystals. This observation suggests the charge transport in the nanocomposites is now governed by acoustic phonon scattering, whereas without graphene, grain boundary scattering limits the mobility in the low temperature range.…”
Section: Weighted Mobilities Of G/sto Nanocompositesmentioning
confidence: 99%
“…We have previously reported that the incorporation of graphene in La doped SrTiO 3 ceramic (sintered conventionally in a reducing atmosphere of Ar/5% H 2 ) resulted in signicant improvement in ZT values. 46 The highest ZT of 0.12 at 1000 K for the base ceramic was improved to values of $0.26 (approximately temperature-independent) from ambient to 1000 K for a graphene loading of 0.6 wt%. More recently Feng et al 47 reported a ZT value of 0.09 at 760 K for pure SrTiO 3 containing RGO, and Okhay et al 48 reported a ZT value of 0.29 at 1160 K for Nb-doped SrTiO 3 containing RGO.…”
Section: Introductionmentioning
confidence: 94%
“…Other impurities may alter the surface energy in ways that could also control the boundary composition and resultant charge state. Other grain boundary engineering strategies such as adding metallic, nanoscale grain boundary phases such as graphene may also improve conductivity and therefore zT .…”
Section: Implications Of Modeling and Strategiesmentioning
confidence: 99%